The Physical Activity and Fitness in Childhood Cancer Survivors (PACCS) Study: Protocol for an International Mixed Methods Study - Lie Hanne C; Anderssen Sigmund; Rueegg Corina Silvia; Raastad Truls; Grydeland May; Thorsen Lene; Stensrud Trine; Edvardsen Elisabeth; Larsen Marie Hamilton; Torsvik Ingrid Kristin; Bovim Lars Peder; Götte Miriam; et al. (JMIR PUBLICATIONS, INC, 2022)
Background
Survivors of childhood cancer represent a growing population with a long life expectancy but high risks of treatment-induced morbidity and premature mortality. Regular physical activity (PA) may improve their long-term health; however, high-quality empirical knowledge is sparse.
Objective
The Physical Activity and Fitness in Childhood Cancer Survivors (PACCS) study comprises 4 work packages (WPs) aiming for the objective determination of PA and self-reported health behavior, fatigue, and quality of life (WP 1); physical fitness determination (WP 2); the evaluation of barriers to and facilitators of PA (WP 1 and 3); and the feasibility testing of an intervention to increase PA and physical fitness (WP 4).
Methods
The PACCS study will use a mixed methods design, combining patient-reported outcome measures and objective clinical and physiological assessments with qualitative data gathering methods. A total of 500 survivors of childhood cancer aged 9 to 18 years with >= 1 year after treatment completion will be recruited in follow-up care clinics in Norway, Denmark, Finland, Germany, and Switzerland. All participants will participate in WP 1, of which approximately 150, 40, and 30 will be recruited to WP 2, WP3, and WP 4, respectively. The reference material for WP 1 is available from existing studies, whereas WP 2 will recruit healthy controls. PA levels will be measured using ActiGraph accelerometers and self-reports. Validated questionnaires will be used to assess health behaviors, fatigue, and quality of life. Physical fitness will be measured by a cardiopulmonary exercise test, isometric muscle strength tests, and muscle power and endurance tests. Limiting factors will be identified via neurological, pulmonary, and cardiac evaluations and the assessment of body composition and muscle size. Semistructured, qualitative interviews, analyzed using systematic text condensation, will identify the perceived barriers to and facilitators of PA for survivors of childhood cancer. In WP 4, we will evaluate the feasibility of a 6-month personalized PA intervention with the involvement of local structures.
Results
Ethical approvals have been secured at all participating sites (Norwegian Regional Committee for Medical Research Ethics [2016/953 and 2018/739]; the Oslo University Hospital Data Protection Officer; equivalent institutions in Finland, Denmark [file H-19032270], Germany, and Switzerland [Ethics Committee of Northwestern and Central Switzerland, project ID: 2019-00410]). Data collection for WP 1 to 3 is complete. This will be completed by July 2022 for WP 4. Several publications are already in preparation, and 2 have been published.
Conclusions
The PACCS study will generate high-quality knowledge that will contribute to the development of an evidence-based PA intervention for young survivors of childhood cancer to improve their long-term care and health. We will identify physiological, psychological, and social barriers to PA that can be targeted in interventions with immediate benefits for young survivors of childhood cancer in need of rehabilitation.